Effect of Curcumin on Docetaxel-Induced Apoptosis in the DU145 (Prostate) Cell Line Using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide Assay - Mohammad Shokrzadeh; Elahe Gharehkhani; Mahboube Rahmati Kukandeh; Mahsa Hosseini (مجله دانشگاه علوم پزشکی گرگان, 2025)
Background and Objective: Prostate cancer is one of the most common malignancies worldwide. Docetaxel (DTX) is proposed as a well-known compound for prostate tumor chemotherapy, and its function is based on inhibiting microtubule depolymerization, disrupting microtubule balance, and consequently delaying cell cycle progression. Complications of DTX include hypersensitivity reactions, red blood cell aggregation, neutropenia, neurological problems, such as paralysis, fluid retention, bronchospasm, refractory hypotension, ADRS, respiratory impairment, cardiac dysfunction, ventricular tachycardia, cystoid macular edema, optic nerve damage, conjunctivitis, and keratopathy. This study aimed to determine the effect of curcumin on DTX-induced apoptosis in the DU145 (prostate) cell line using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Methods: This descriptive analytical study was conducted on the DU145 (prostate) cell line, purchased from the National Genetic Resources Cell Bank, at the Cell Culture Laboratory of the F aculty of Pharmacy, Mazandaran University of Medical Sciences. Cells were passaged for exposure to the desired drugs. Groups included curcumin at concentrations of 2, 4, 6, 8, and 10 µg/mL and DTX at a concentration of 4.46 µg/mL. Cells were incubated in triplicate for 24 hours. For the MTT assay, the culture rate was 104 cells per well. Apoptosis testing was designed for four groups (DTX at a concentration of 4.46 µM, curcumin at a concentration of 2 µM combined with DTX at an optimal concentration, curcumin at a concentration of 10 µM combined with DTX at an optimal concentration, and curcumin at a concentration of 10 µM alone), with the culture rate of 5×105 cells per well in 6-well plates. After cell exposure, MTT and apoptosis determination assays were performed. Results: DTX reduced the viability of DU145 (prostate) cells by approximately 50% (P<0.05). Groups treated with curcumin combined with DTX showed a dose-dependent decrease in cytotoxicity and an increase in the viability of DU145 (prostate) cells (P<0.05). Additionally, curcumin was able to reduce apoptosis in DU145 (prostate) cells by 90%. Conclusion: Curcumin increases cell viability and reduces apoptosis in DU145 (prostate) cells.